1. x-2y=11–>x=2y+11
2. Substitute the value of x into the first equation: -7(2y + 11) - 2y = -13
3. Simplify the equation: -14y - 77 - 2y = -13
4. Combine like terms: -16y - 77 = -13
5. Move the constant term to the other side: -16y = 64
6. Solve for y: y = -4
7. Substitute the value of y into the second equation: x - 2 (-4) = 11
8. Simplify the equation: x + 8 = 11
9. Solve for x: x = 3
10. The solution to the system of equations is (3, -4)
Put the steps in order that are used to solve the following systems of equations by substitution.
-7х - 2y = -13
x-2y = 11
(Put the numbers listed below in order that are used to solve this equation)
x+8 = 11
X = 3
-14y - 77 - 2y = -13
(3, -4)
-16y - 77 = -13
-16y = 64
x-2y=11–>x=2y+11
-7(2y + 11) - 2y = -13
y = -4
x - 2 (-4) = 11
1 answer